2005
DOI: 10.1093/nar/gki924
|View full text |Cite
|
Sign up to set email alerts
|

8-Methyl-2'-deoxyguanosine incorporation into parallel DNA quadruplex structures

Abstract: This paper concerns the Circular Dichroism (CD) and Nuclear Magnetic Resonance (NMR) structural studies of the quadruple helix arrangements adopted by three tailored oligodeoxyribonucleotide analogues, namely d(TGMeGGT), d(TGGMeGT) and d(TGGGMeT), where dGMe represents a 8-methyl-2′-deoxyguanosine residue. The results of this study clearly demonstrate that the effects of the incorporation of dGMe instead of a dG residue are strongly dependant upon the positioning of a single base replacement along the sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
56
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 36 publications
9
56
0
Order By: Relevance
“…NMR data for T12 and F12 are compatible with the formation of tetramolecular parallel quadruplex structures characterized by an all- syn tetrad at the 5′ end and two (for T12 ) or three (for F12 ) all- anti tetrads for the other purines (Figure 5). These results are in agreement with those obtained for monosubstituted TG 3 T and TG 4 T in the first and second positions, folding in quadruplex structures in which the modified guanosines form all- syn tetrads only if positioned at the 5′-end side (33,34).
Figure 5.Schematic representation of the quadruplexes formed by T12, T13, F12, F13, F14 and F24 .
…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…NMR data for T12 and F12 are compatible with the formation of tetramolecular parallel quadruplex structures characterized by an all- syn tetrad at the 5′ end and two (for T12 ) or three (for F12 ) all- anti tetrads for the other purines (Figure 5). These results are in agreement with those obtained for monosubstituted TG 3 T and TG 4 T in the first and second positions, folding in quadruplex structures in which the modified guanosines form all- syn tetrads only if positioned at the 5′-end side (33,34).
Figure 5.Schematic representation of the quadruplexes formed by T12, T13, F12, F13, F14 and F24 .
…”
Section: Resultssupporting
confidence: 91%
“…This arrangement is consistent with that of the quadruplex structures adopted by the monosubstituted ODNs TMGGGT and TGGGMT, in which the M residues form an all- syn tetrad in both cases (33). …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It has been reported that the inclusion of two 8-methyl-2′-deoxyguanosine (M) residues in d(TMGMGT) promotes the formation of an unprecedented antiparallel tetra-stranded G4 in which two adjacent strands run in the same direction (59). Since a bromine atom has a similar size as a methyl group and the 8-bromoguanine residue has the same tendency to promote a syn glycosidic conformation (7,6062), we investigated the assembly properties of d(TG Br GG Br GAC 7 ), where G Br indicates an 8-bromoguanine residue. Figure 3B shows that under acidic conditions d(TG Br GG Br GAC 7 ) forms tetrameric ions with three NH 4 + ions corresponding to tetramolecular G4 structures ([4M + 3NH 4 ] 8− at m/z 2032.45; [4M + 3NH 4 ] 7− at m/z 2322.97).…”
Section: Resultsmentioning
confidence: 99%
“…[9] Interestingly, tetramolecular all-trans quadruplexes [TG [3][4] T] 4 lacking intervening loop sequences are often prone to changes in tetrad polarity through the introduction of syn-favoring 8-Br-dG or 8-Me-dG analogues. [10] By changing the polarity of the ODN 5'-terminal tetrad, the antiparallel G-tract and each of the three parallel G-tracts exhibit a non-alternating all-syn and all-anti array of glycosidic torsion angles, respectively. This particular glycosidicbond conformational pattern is unique, being unreported in any known quadruplex structure, expanding the repertoire of stable quadruplex structural types as defined previously.…”
mentioning
confidence: 99%